Peran Guru Pendidikan Agama Islam dalam Membentuk Sikap Toleransi Beragama dan Sosial di Sekolah Dasar: Systematic Literature Review - Larasati, Dinda Kenanga; Larasati, Dinda Cempaka; Dewi, Ayu Mustika (Journal of Research and Thought on Islamic Education (JRTIE), 2024)
The development of the times has a big influence on a person's attitudes and morals. Therefore, to avoid negative currents, education is needed, one of which is religious education. Religious education is generally applied at the elementary school level, namely in Islamic Religious Education subjects. At the elementary school level, children's development begins to be concrete, rational, and objective, so at this age, it is very necessary to form individuals who can have and apply social attitudes and tolerance towards other people. The research aims to determine the role of PAI teachers in forming social attitudes and religious tolerance in elementary schools. This type of research uses the Systematic Literature Review (SLR) research method. The databases used in this research are Google Scholar and GARUDA with articles ranging from 2015-2024. The data obtained from Google Scholar amounted to 62 articles, and only 6 articles were relevant to the context, while the data obtained from GARUDA amounted to 16 articles, and only 1 article was relevant to the context. The results of the research show that PAI has a fairly large role in the world of education, especially in shaping individual character and morals. In the PAI learning process, teachers apply group learning methods that involve students in real action. The learning method applied is considered successful in learning. Apart from the group learning method, there is also the role-playing method. Apart from these two methods, it turns out there is another method that is considered effective, namely the simulation method. PAI teachers model tolerance and social behavior in everyday life so they can be good examples for their students.